James H. Sherman correspondence - Sherman, James H. (James Henry)
Letters written by Sherman to his wife, Phebe A.G. Sherman, of New Bedford, Mass., while he served as first mate on the whaleship Milton during its voyage to the Pacific Ocean (1873 October 8-1876 October 24). Most letters were written from whaling grounds near New Zealand and describe activities and events aboard the Milton and details about whaling. The letters also reflect the religious faith of Sherman and his wife.
Whaler. Born 1844.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Sherman, Phebe A. G. -- Correspondence; Milton (Ship); Seafaring life; Whaling -- Massachusetts -- New Bedford; Whaling -- New Zealand; Whaling -- Pacific Ocean; New Bedford (Mass.) -- Religious life and customs; Whalers (Persons)